2004
DOI: 10.1213/01.ane.0000111208.08867.3c
|View full text |Cite
|
Sign up to set email alerts
|

Postcesarean Analgesia with Spinal Morphine, Clonidine, or Their Combination

Abstract: A multimodal approach to postcesarean analgesia, using subarachnoid bupivacaine, fentanyl, morphine 100 microg, and clonidine 60 microg, improves pain relief compared with morphine 100 microg or clonidine 150 microg alone, but increases intraoperative sedation and may increase perioperative vomiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 20 publications
7
65
0
2
Order By: Relevance
“…In sufentanil group, patients were calm and sleepy. These results corroborate the findings of previous studies, which demonstrated the anxiolytic activity of clonidine and sufentanil 3,23,27,28 . However, in Groups I and III, patients were awake and anxious due to perioperative pain, especially in the group without adjuvant, and required midazolam.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In sufentanil group, patients were calm and sleepy. These results corroborate the findings of previous studies, which demonstrated the anxiolytic activity of clonidine and sufentanil 3,23,27,28 . However, in Groups I and III, patients were awake and anxious due to perioperative pain, especially in the group without adjuvant, and required midazolam.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we used morphine (100 µg), a dose often recommended for subarachnoid space application in cesarean section, combined with hyperbaric bupivacaine with or without other adjuvants. At this dosage, the incidence of late adverse effects is lower and does not affect the quality of postoperative analgesia 6,[19][20][21][22][23][24][25] . Due to morphine side effects and slow onset of action, liposoluble opioids (fentanyl and sufentanil) are used intrathecally in combination with local anesthetics for cesarean section.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[82] Other studies have found that 75 µg is a safe dose; prolong the anaesthetic block and enhance postoperative analgesia, with minimal side effects and no harm to the newborn. [83,84,85] In a randomized, double blind, dose finding study, Peach et al [86] compared intrathecal clonidine mixed with fentanyl and morphine versus clonidine plus morphine in 240 women undergoing cesarean section with hyperbaric 0.5% bupivacaine. A dose-finding analysis showed similar postoperative efficacy and side effects for groups receiving morphine 100µg with clonidine 60, 90, or 150 µg and concluded that a multimodal approach to postcesarean analgesia, using subarachnoid bupivacaine, fentanyl, morphine 100 µg, and clonidine 60 µg, improves pain relief compared with morphine 100 µg or clonidine 150 µg alone, but increases intraoperative sedation and may increase perioperative vomiting.…”
Section: Obstetricsmentioning
confidence: 99%